Roles of Curcumin and Monochromatic Light in Optimizing Liver Function to Support Egg Yolk Biosynthesis in Magelang Ducks - Kasiyati; Sumiati; Ekastuti, Damiana Rita; Manalu, Wasmen (International Journal of Poultry Science, 2016)
Backgroud: The biosynthesis of vitellogenin as an egg-yolk precursor in oviparous animals is occurred in the liver cells. The vitellogenin synthetic capacity of hepatocyte is under the control of estrogen that its secretion increase when the oviparous animals reach sexual maturity. This experiment was designed to study the uses of curcumin and artificial monochromatic light on liver performance to improve vitellogenin synthesis to support egg production during laying period. Materials and Methods: One hundred and ninety two female magelang ducks were assigned into a completely randomized design with a 4×4 factorial arrangement. The first factor was dose of curcumin supplementation consisted of 4 levels i.e., 0, 9, 18 and 36 mg. The second factor was the color of monochromatic light consisted of 4 levels i.e., white, red, green and blue. Results: The results showed the interaction effects between curcumin and monochromatic light on the liver weight, hepatocytes diameter, DNA and RNA concentrations in the liver cells (p<0.05). Serum estradiol and vitellogenin concentrations in female magelang ducks during sexual maturity prior to laying period ranged from 0.06-0.19 and 0.36-3.46 mg mL–1, respectively. Curcumin supplementation at doses of 18 and 36 mg duck–1 day–1 increased the diameters of F1 follicles by 21.62 and 17.91%, respectively. Conclusion: It is concluded that curcumin supplementation at a dose of 18 mg duck–1 day–1 combined with the use of red or greenlight can improve the biosynthesis capacity of egg yolk protein precursors by liver cells without increasing liver cells proliferation. Moreover, the increased estradiol during vitellogenesis is also necessary in the recruitment of ovarian follicles in establishing the F1 hierarchical follicles.